High-Urgency Renal Transplantation: Indications and Long-Term Outcomes - Lampros Kousoulas; Nikos Emmanouilidis; Wilfried Gwinner; Jürgen Klempnauer; Frank Lehner (Journal of Transplantation)
The concept of high-urgency (HU) renal transplantation was introduced in order to offer to patients, who are not able to undergo long-term dialysis treatment, a suitable renal graft in a short period of time, overcoming by this way the obstacle of the prolonged time spent on the waiting list. The goal of this study was to evaluate the patient and graft survivals after HU renal transplantation and compare them to the long-term outcomes of the non-high-urgency renal transplant recipients. The clinical course of 33 HU renal transplant recipients operated on at our center between 1995 and 2010 was retrospectively analyzed. The major indication for the HU renal transplantation was the imminent lack of access for either hemodialysis or peritoneal dialysis (67%). The patient survival of the study population was 67%, 56%, and 56%, whereas the graft survival was 47%, 35% and 35%, at 5, 10, and 15 years, respectively. In the comparison between our study population and the non-HU renal transplant recipients, our study population presented statistically significant (P<0.05) lower patient survival rates. The HU renal transplant recipients also presented lower graft survival rates, but statistical significance (P<0.05) was reached only in the 5-year graft survival rate.